Original paperThe evaluation of treatment plans in high-dose-rate endobronchial brachytherapy by utilizing 2D and 3D computed tomography imaging methods - Sawicki, Marcin; Kazalski, Damian; Łyczek, Jarosław; Kowalik, Łukasz (Journal of Contemporary Brachytherapy, 2014)
Purpose : To present comparison of treatment plans made by using 2D and 3D methods in the planning system, as well as to assess the quality of treatment plans using the 2D and 3D methods. Material and methods: The studies involved a group of 31 patients with advanced lung cancer treated in the Brachytherapy Department of the Subcarpathian Cancer Center in Brzozów from 2011 to 2013. In total, 31 patients and 76 treatment plans were analyzed. We compared coverage of PTV planned in 3D and 2D. In the 3D method of treatment, three-dimensional images from computer tomography were used. In treatment plans performed using the 2D method, images from the simulator were used. Results : The comparison of treatment plans made by using 2D and 3D methods is described. This comparison highlighted the significant differences between these two methods assessing reference dose coverage of the PTV by 100% and 85% isodose. Conclusions : Reference doses with 100% coverage of the PTV in treatment applied with the 3D method are 31% higher than when applied with the 2D method.